Carcass and meat characteristics of male chickens between Thai indigenous compared with improved layer breeds and their crossbred - Jaturasitha S. (2014)
The study of carcass and meat quality of four male genotypes namely: Thai native (TH), crossbred (Thai native x Barred Plymouth Rock; THB), Barred Plymouth Rock (BPR) and Shanghai (SH) chickens was conducted. Three hundred and twenty birds receiving from four equal groups were allotted in Completely Randomized Design (CRD). They were fed from one day and slaughtered at 16 weeks of age. Breast (M. pectoralis major) and thigh (M. biceps femoris) muscles were investigated for meat quality. TH had lower slaughtered weight (P<.001) but higher lean : bone as well as less bone percentage (P<0.05) than all groups. Thigh muscle fiber of TH had higher type I and lower type UB whereas there were similar in breast muscle fiber. Meat quality in terms of IMF, cholesterol and triglyceride contents as well as n-3 fatty acid and the ratio of n-6/n-3 of Thai indigenous male strain was more favorable compared to those all genotypes. Breast and thigh muscle were higher in shear force value and collagen content but the sensory evaluation was not significantly different. Since they were similar in sensory evaluation, the male layer and the male crossbred chickens have the potential to substitute TH in a market serving consumers who prefer chewy chicken meat.